2020
DOI: 10.1186/s12872-020-01756-y
|View full text |Cite
|
Sign up to set email alerts
|

Blood group A: a risk factor for heart rupture after acute myocardial infarction

Abstract: Introduction Studies have been performed to identify the association between ABO blood groups and coronary artery disease. However, data is scarce about the impact of ABO blood groups on heart rupture (HR) after acute myocardial infarction (AMI). Methods We conducted a retrospective case–control study that included 61 consecutive patients with HR after AMI during a period from 1 January 2012 to 1 December 2019. The controls included 600 patients who were selected randomly from 8143 AMI patients without HR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…A case-control study showed that blood group A was significantly associated with an increased risk of cardiac rupture after acute MI after adjustment for confounders. This finding was attributed to the larger infarct size and more extensive myocardial necrosis in non-O blood group patients, 2 which may have been due to poor collateral circulation. 35,36 A study on patients with acute MI showed using multivariate analysis that blood group O was independently and positively associated with spontaneous recanalization of the culprit coronary artery.…”
Section: Prognosis Of Patients With Cad and Acsmentioning
confidence: 99%
See 2 more Smart Citations
“…A case-control study showed that blood group A was significantly associated with an increased risk of cardiac rupture after acute MI after adjustment for confounders. This finding was attributed to the larger infarct size and more extensive myocardial necrosis in non-O blood group patients, 2 which may have been due to poor collateral circulation. 35,36 A study on patients with acute MI showed using multivariate analysis that blood group O was independently and positively associated with spontaneous recanalization of the culprit coronary artery.…”
Section: Prognosis Of Patients With Cad and Acsmentioning
confidence: 99%
“…A case-control study showed that blood group A was significantly associated with an increased risk of cardiac rupture after acute MI after adjustment for confounders. This finding was attributed to the larger infarct size and more extensive myocardial necrosis in non-O blood group patients, 2 which may have been due to poor collateral circulation. 35,36…”
Section: Prognosis Of Patients With Cad and Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] The importance of the ABO blood groups' role in CAD patients' prognosis has been reported in some previous studies,[ 15 ] and some of them had not been confirmed this association. [ 16 17 18 19 ] A significant correlation between blood Group A and the higher risk of postacute M heart rupture has been reported in Fu et al . 's study in univariate as well as multivariate analyses that was the first study considering the blood group as an independent risk factor for heart rupture in Chinese subjects with acute myocardial infarction .…”
Section: Discussionmentioning
confidence: 79%
“…In a study of 1209 patients with acute myocardial infarction, Lin et al found a higher rate of spontaneous recanalization following myocardial infarction in association with the O blood group whereas the rate of spontaneous recanalization was lower in subjects with an A blood group [28]. Blood group A type has also been associated with an increased risk of heart rupture following myocardial infarction [29]. Hence, ABO blood type may not only predispose susceptible individuals to an increased risk of CVD events but may also influence post-myocardial infarction outcomes.…”
Section: Abo and Coronary Artery Diseasementioning
confidence: 99%